Unveiling the Landscape of ClassDojo in Education: A Systematic Review - Putrie, Delitya Islamy; Salam, Urai; Riyanti, Dwi (Universitas Lancang Kuning, 2024)
In the backdrop of the evolving game-based educational platforms from online resources, language researchers have directed their attention toward the utilisation of ClassDojo due to its multifunctionality, which includes many features such as attendance tracking, messaging, portfolio management, games, and more. This qualitative systematic review examined the existing research on using ClassDojo in the classroom. The purposes were to provide evidence of ClassDojo for teachers, students, or parents and to identify the study characteristics, such as the publication trends, participant profiles, or the methodological approaches from the published research about ClassDojo. The initial database search used Publish and Perish (PoP) version 8 and identified as many as 174 published research. However, twenty-three journal articles were selected after conducting the screening process by applying inclusion and exclusion criteria. Results from the analysis of 23 articles found that articles released in 2021 (n = 6) were the most frequently used in this systematic review study. Then, for the education level of participants, the elementary education settings received the most attention (n = 6). Additionally, experimental design (n = 7) was the methodology most frequently employed by the study under investigation. Furthermore, the reviewed studies also show that ClassDojo is mainly used as a teaching and learning media (n = 8). Thus, the productive use of ClassDojo was recommended because it can effectively manage student behavior, promote positive classroom management, and enhance parent engagement. Therefore, ClassDojo can potentially enhance online interaction in the class and provide a community to share classroom activities privately or publicly among teachers, students, and parents.